Design and Coordination of Cooperative Mobile Robots - Mohamed Krid (Institute of Advanced Engineering and Science, 2016)
Object transportation is an important task considered in mobile robotics. For many years, it has been performed by single robots, capable to transport payload of moderate size and mass with respect to the robot size and mass. But if the payload gets bigger, the robot fails in the transporting task. For wider or heavier payloads, human operators improve their capacities by working in group. A similar improvement should be expected with a group of mobile robots.In this paper, we proposed a new concept of cooperative mobile robots to deal with the problem of long object transportation in unstructured environment whatever the payload length. The proposed C3Bots AT/VLP robot is formed by the association of two or more mono-robots with simple kinematics forming a poly-robot system.The paper presents several kinematic schemes and the corresponding obstacle-crossing processes. It deals with the problem of how to maintain stable motion for the poly-robot during obstacle crossing. Changes in the internal configuration of the robot adjust the center of gravity to guarantee stable motion. A specific stability criterion for contact on three wheels is presented. By adjusting the relative poses of the front and rear axles with respect to the payload, it is possible to maximize the stability of the poly-robot and its payload during obstacle crossing.